Perbaikan Aliran Proses Sertifikasi di LSP X Menggunakan Metode Value Stream Mapping (VSM) - Sutanto, Marko Yuli; Sholeh, Ibnu; Hasbullah, Hasbullah (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
Industrial Engineering and Management Professional Certification Institute (LSP X) is an institution that has been licensed by BNSP to conduct competency tests in accordance with the scheme. As an independent and professional institution in the Industrial Engineering and Management sector, there is a longer time difference between the real time certification process and the time determined by the X LSP for 14 days. The purpose of this research is to improve the flow of the certification process in order to accelerate the time faster (7 days) by eliminating activities that do not add value to the certification process at LSP X and identifying what factors cause the certification process time to be longer than the standard. determined by LSP X and conducted by the value stream mapping method. current state mapping is made to identify waste, then future state mapping is made to make improvements. The research results obtained from this case study show that in the certification process at the X LSP, the certification process time can be accelerated, activity grouping, waste analysis and time analysis so that it can get a faster time in the certification process compared to the previous one, namely by comparing the length of time of the Current State certification. 14 days and 7 days future state using the efficient and effective Value Stream Mapping (VSM) method.